Assessing psychological inflexibility in infertility: The development and validation study of the Psychological Inflexibility Scale – Infertility (PIS-I) - Galhardo, Ana (2022)
Facing an infertility diagnosis and the demands of infertility medical treatment has been widely recognized as a psychologically distressing condition and psychological inflexibility may be a relevant construct to better understand mental health in this population. In this context, the current study aimed to develop a new self-report measure, the Psychological Inflexibility Scale – Infertility (PIS–I), and examine its factor structure and psychometric properties. Based on the Acceptance and Commitment Therapy (ACT) conceptual framework, literature review and clinical expertise in the infertility domain, an initial pool of 18 items was developed. An online survey was conducted with 287 women presenting an infertility diagnosis. Exploratory Factor Analysis revealed that a refined version of the PIS-I, encompassing 16 items, presented a single-component structure accounting for 58.92% of the variance. Psychometric analyses showed an excellent internal consistency and support for the PIS-I convergent, concurrent, and incremental validities was found. Overall, the PIS-I showed to be a context-specific reliable and valid measure of psychological inflexibility for people dealing with infertility, being useful for clinical and research purposes.